A Nordic graduate school in mathematics education starts in 2004 - Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2004)
Nordisk Forskeruddannelsesakademi, NorFa, has decided to support a Nordic graduate school in mathematics education for the period 2004–2008.